(untitled) - Food and Agriculture Organization of the United nations (Rome, 2007)
These proceedings present an outcome of the Methodological Workshop on the management of Tuna Fishing CapacityL Stock Status, Data Envelopment Analysis, industry surveys and management options.It was hosted by the Inter-America form 8 to 2 may 2006.
Keywords: Tuna fisheries,Tuna industry,Cá ngừ,Ngành công nghiệp cá ngừ